Prevalence and mechanisms of azole resistance in clinical isolates of Aspergillus section Fumigati species in a Canadian tertiary care centre, 2000 to 2013. (31st December 2019) - Parent-Michaud, Maxime; Dufresne, Philippe J; Fournier, Eric; Folch, Benjamin; Martineau, Christine; Moreira, Sandrine; Doucet, Nicolas; De Repentigny, Louis; Dufresne, Simon F
Abstract: Objectives: Azole resistance among Aspergillus fumigatus isolates is a growing concern worldwide. Induction of mutations during azole therapy, environment-acquired mutations caused by azole fungicides and intrinsic resistance of cryptic Fumigati species all contribute to the burden of resistance. However, there is a lack of data in Canada on this emerging threat. Methods: To gain insights into the magnitude and mechanisms of resistance, a 14 year collection of Aspergillus section Fumigati comprising 999 isolates from 807 patients at a Montreal hospital was screened for azole resistance, and resistance mechanisms were investigated with the combined use of genome sequencing, 3D modelling and phenotypic efflux pump assays. Results: Overall azole resistance was low (4/807 patients; 0.5%). A single azole-resistant A. fumigatus sensu stricto strain, isolated from a patient with pulmonary aspergillosis, displayed efflux-pump-mediated resistance. Three patients were colonized or infected with azole-resistant cryptic Fumigati species (one Aspergillus thermomutatus, one Aspergillus lentulus and one Aspergillus turcosus ). Evidence is presented that azole resistance is efflux-pump-mediated in the A. turcosus isolate, but not in the A. lentulus and A. thermomutatus isolates. Conclusions: Azole resistance is rare in our geographic area and currently driven by cryptic Fumigati species. Continued surveillance of emergence of resistance is warranted.